Mechanical harvesting in tea: A case study of Pasuparai estate - Ajaikumar, S.; Mathew, Siby; Kumar, R. Raj; Kumar, P. Mohan (Journal of Plantation Crops, 2014)
Tea cultivation is a highly labour intensive and more than 2.0 lakh people are directly or indirectly involved in south India. Normally, women workers are deployed to harvest the crop manually at an interval of 10-12 days. By the turn of the century, usage of hand held shears became inevitable to increase the labour productivity. An interval of 14-16 days is mandatory to obtain good quality and regular crop production when hand held shears are used. Employing more labour is not practically and economically viable and hence adoption of mechanical harvesting is the only option to achieve the sustainability of the crop. The case study deals with continuous mechanization over a period of 6 years and its impact on crop productivity besides the adoption of improved agronomic practices. Significant improvement in plucking average was recorded after the introduction of machines. Timely harvesting of the crop improved the quality parameters of made tea and reduced the cost of harvesting. Deliberate addition of a new tier of maintenance foliage was followed during January-March, every year after the machine harvesting. Furthermore, foliar application of micronutrients, plant growth regulators and potassium nitrate also given to minimize the ill effects of mechanization. Mechanization enabled to achieve sustained crop productivity, and the case study narrates the impact of mechanization and the importance of adopting good agronomic practices to sustain the productivity in south Indian tea plantations.